1990
DOI: 10.1098/rspb.1990.0024
|View full text |Cite
|
Sign up to set email alerts
|

A model of quantitative traits under frequency-dependent balancing selection

Abstract: We describe a computer model that stimulates a combination of stabilizing and frequency-dependent selection acting on a quantitative character determined by several loci. The results correspond to many features of natural variations at both the phenotypic and genotypic levels. The model is robust, and its results are not strongly dependent either on the nature and shape of the function describing the stabilizing selection, or on the precise form of frequency dependence, except near the extrema. It suggests a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Moreover, correlational selection often results from frequency-dependent interactions such as those between predators and prey, or parasites and hosts [28]; frequency-dependence can easily result in stable polymorphisms [2] and stable quantitative variation [29]. Provided that phenotypic correlations are consistent and based upon some genetic correlation, this can favour variation in both traits.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, correlational selection often results from frequency-dependent interactions such as those between predators and prey, or parasites and hosts [28]; frequency-dependence can easily result in stable polymorphisms [2] and stable quantitative variation [29]. Provided that phenotypic correlations are consistent and based upon some genetic correlation, this can favour variation in both traits.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic variation in threshold traits is likely to be largely a function of frequency-dependent selection or a result of phenotypic plasticity (induction of protective structures in the presence of a predator cue; Roff, 1994bRoff, , 1996. This type of selection can readily preserve phenotypic variation and can play an important role in the preservation of genetic variation in quantitative traits (Mani et al, 1990;Roff, 1997a). Its importance in maintaining genetic variation in threshold traits is explored elsewhere (Roff, 1997b).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical studies have demonstrated the diversifying effects of inverse frequency-dependent selection (Mani et al 1990, Andreasen and Christiansen 1995, Cressman 1996, Hammerstein 1996. Frequency-dependent selection has been studied in predatorÐprey systems (Dale et al 1994) and in seedling dynamics of tropical trees (Augspurger and Kitajima 1992).…”
mentioning
confidence: 98%